Strengthening Hydromet and Early Warning Systems and Services in Georgia : A Road Map - World Bank (World Bank, Washington, DC, 2021)
This analytical work assesses the current capabilities of, as well as the gaps and challenges faced by, the Georgian Hydrometeorological Department (GHMD) in producing and delivering weather, climate, and hydrological (hydrometeorological) products and services based on users’ needs. It provides the government authorities and decision makers in Georgia with a technical strategic framework for improvements in hydromet and early warning systems and services (EWS), to provide socioeconomic benefits to the Georgian population; safeguard their lives, livelihoods, and property; and protect economic investments. The road map consists of 11 chapters. Chapters 1-3 highlight the climate and hydrological hazards affecting Georgia, their consequent risks, and the socioeconomic impacts on the Georgian people. Chapter 4 provides an assessment of users’ needs for hydromet information. Chapter 5 gives an overview of the institutional and organizational structure of GHMD, while chapter 6 provides an in-depth analysis of GHMD’s current status. Chapter 7 discusses modernization of hydromet and EWS. Chapters 8 and 9 present the road map in detail, along with three proposed successive development scenarios designed to transform GHMD into a technically modern and sound hydrometeorological service by narrowing the gap between GHMD’s current status and the level of services needed for fully discharging its public service mandate. Chapter 10 presents a detailed socioeconomic benefits analysis. Finally, chapter 11 lays out the conclusions and a way forward, and several annexes provide additional details.